141k views
2 votes
Find the average rate of change for f(x) = x2 − 3x − 10 from x = 4 to x = 6. A) 5 B) 7 C) 9 D) 11

User Dwardu
by
6.4k points

1 Answer

4 votes

Answer:

The rate of change between these on average is 7

Explanation:

In order to find these, we need to evaluate the equation at both points.

x^2 - 3x - 10

4^2 - 3(4) -10

16 - 12 - 10

-6

This gives us the ordered pair of (4, -6)

x^2 - 3x - 10

6^2 - 3(6) - 10

36 - 18 - 10

8

This gives us the ordered pair of (6, 8)

Now we use these two points in the slope formula to find the rate of change.

m(slope) = (y2 - y1)/(x2 - x1)

m = (8 - -6)/(6 - 4)

m = 14/2

m = 7